Automatic molecular structure perception for the universal force field. Issue 13 (1st March 2016) - Artemova, Svetlana; Jaillet, Léonard; Redon, Stephane
Abstract : The Universal Force Field (UFF) is a classical force field applicable to almost all atom types of the periodic table. Such a flexibility makes this force field a potential good candidate for simulations involving a large spectrum of systems and, indeed, UFF has been applied to various families of molecules. Unfortunately, initializing UFF, that is, performing molecular structure perception to determine which parameters should be used to compute the UFF energy and forces, appears to be a difficult problem. Although many perception methods exist, they mostly focus on organic molecules, and are thus not well‐adapted to the diversity of systems potentially considered with UFF. In this article, we propose an automatic perception method for initializing UFF that includes the identification of the system's connectivity, the assignment of bond orders as well as UFF atom types. This perception scheme is proposed as a self‐contained UFF implementation integrated in a new module for the SAMSON software platform for computational nanoscience (http://www.samson-connect.net ). We validate both the automatic perception method and the UFF implementation on a series of benchmarks. Abstract : The Universal Force Field (UFF) is a classical force field applicable to almost all atom types of the periodic table. This article proposes an automatic perception method for initializing UFF that includes the identification of the system's connectivity, the assignment of bond orders as well as UFF atom types. This perception scheme is proposed as a self‐contained UFF implementation integrated in a new module for the SAMSON software platform for computational nanoscience.